Relational Exchange and the Degree of Embeddedness: An Empirical Study of Supply Chains - Radaev, Vadim (Journal of Economic Sociology, 2016)
This paper focuses on the relational aspect of embeddedness and examines direct interfirm exchange in supply chains. We distinguish between the transactional and the relational forms of exchange and construct an original typology of their constitutive elements, which we attach to the phases of the interfirm contract cycle. An index of relational exchange is built measuring the degree of embeddedness in the supply chain relationships. Regression models are used to reveal the factors that facilitate relational exchange, including the firms’ location in the supply chain, the type of product, and the intensity of the interactions between exchange partners. Empirical data were collected by the author and the research team in 2010 from the grocery and home electronic appliances sectors, which account for approximately 50% of sales in Russian retailing. In total, 512 questionnaires were completed by the managers of retail chains and their suppliers in five of Russia’s cities, including Moscow, St. Petersburg, Yekaterinburg, Novosibirsk, and Tyumen. On average, 50 retailers and 50 suppliers were interviewed in each city area.